Animals in the Periodic Table! - Joshi, Bhawisha (Homœopathic Links, 2015)
This article summarises the recent work of Dr. Shachindra Joshi and Dr. Bhawisha Joshi on remedy relationships. The Joshis see a clear trend of comparable similarities between mineral, plant and animal remedies. They have extensively worked on the mineral and animal correspondences and some of that work is explained here. These correspondences can be used to switch from mineral to animal remedies or vice versa. These correspondences can also be used in difficult animal cases where you may first plot a person on the Periodic Table and then find the appropriate animal counterpart to that row to find and prescribe an animal remedy. This novel and unique concept has been clinically verified in their own practice and also by several homoeopaths across the globe.
Keywords: Animal kingdom; Periodic Table; Animal; Mineral correspondence; Remedy relationships; Changing remedies